Intelligent CALL, Granular Systems and Learner Data: Short Papers From Eurocall 2022 2022
DOI: 10.14705/rpnet.2022.61.1476
|View full text |Cite
|
Sign up to set email alerts
|

The use of machine translation in L2 education: Japanese university teachers’ views and practices

Abstract: Machine Translation (MT) is receiving increasing attention within language education due to both its affordances and the potential it offers for academic misconduct. To understand more about teachers’ views and practices, a survey was conducted with 153 foreign language (L2) educators who teach at Japanese universities. The survey examined their; (1) use of MT to assist with L2 reading, writi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…Teachers who had used ChatGPT before had significantly higher positive impact scores (M = 0.26) compared to non-users (M = -0.26; t = 5.53, p < 0.001). This aligns with findings from research on machine translation conducted with language teachers (Ohashi, 2022) and a study with teachers of various subjects that found using ChatGPT more frequently led to more positive perspectives (Kaplan-Rakowski et al, 2023). However, there was no significant difference in negative impact scores between these groups.…”
Section: Perceived Impact Through Quantitative Analysissupporting
confidence: 82%
See 3 more Smart Citations
“…Teachers who had used ChatGPT before had significantly higher positive impact scores (M = 0.26) compared to non-users (M = -0.26; t = 5.53, p < 0.001). This aligns with findings from research on machine translation conducted with language teachers (Ohashi, 2022) and a study with teachers of various subjects that found using ChatGPT more frequently led to more positive perspectives (Kaplan-Rakowski et al, 2023). However, there was no significant difference in negative impact scores between these groups.…”
Section: Perceived Impact Through Quantitative Analysissupporting
confidence: 82%
“…Teachers expressed a mix of optimism about the benefits of efficiency and self-directed learning, and caution about enabling academic misconduct and over-reliance. Direct experience with ChatGPT was associated with more positive perspectives, consistent with patterns from research on machine translation tools (Ohashi, 2022). Adoption is clearly at an early stage of development.…”
Section: Discussingsupporting
confidence: 76%
See 2 more Smart Citations